Experimental Study on the Multikeyed Joints of Concrete and Reinforced Concrete Elements - Dovzhenko, Oksana; Pohribnyi, Volodymyr; Karabash, Leonid (International Journal of Engineering and Technology, 2018)
The connections ensure teamwork under the load of buildings and structures bearing elements. Joints distraction leads to a change in the structures support conditions and their design schemes. Keyed joints are the most effective under significant shear force action because they have high shear resistance. This makes it necessary to further improve their design solutions. In the article the experimental study results of multikeyed joints two series are presented. The joint models were tested in the department laboratory of reinforced concrete and stone structures and resistance of materials Poltava National Technical Yuri Kondratyuk University. The keyed profile (keyâ€™s depth to height ratio and load application surface angle), reinforcement (quantity of reinforcement and its location character), seam width, keys number were varied in experiments. Heavy-weight concrete, expanded clay concrete and polypropylene fiber concrete were used for the samples manufacture. In experiments the influence of one of listed factors and their combinations for bearing capacity were studied. The concrete and reinforcement strains, distraction character, the failure load were studied. The influence degree analysis of the factors determining the strength was carried out. The design joints parameters that correspond to maximum strength were determined.Â Â
Keywords: Joint; Connection; Factors of influence; Strength